-(3x-7)+6x=29

Simple and best practice solution for -(3x-7)+6x=29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(3x-7)+6x=29 equation:


Simplifying
-1(3x + -7) + 6x = 29

Reorder the terms:
-1(-7 + 3x) + 6x = 29
(-7 * -1 + 3x * -1) + 6x = 29
(7 + -3x) + 6x = 29

Combine like terms: -3x + 6x = 3x
7 + 3x = 29

Solving
7 + 3x = 29

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 3x = 29 + -7

Combine like terms: 7 + -7 = 0
0 + 3x = 29 + -7
3x = 29 + -7

Combine like terms: 29 + -7 = 22
3x = 22

Divide each side by '3'.
x = 7.333333333

Simplifying
x = 7.333333333

See similar equations:

| -13-5x=6-6x | | 9x^3+27x^2-x-3=0 | | 9x^3-19x^2-24x=0 | | -x+3=y-2-2 | | 0=10x^2-360 | | f+4=76 | | e*f-3m=x | | 5(10-6x)=200 | | (3t-8)(t-1)=0 | | -(r+7)+1=-3(-8r+2) | | 10(2x+4)=-1(-8-9x)+3 | | 2x-(3x+4)= | | x^2-2=18 | | 2mn= | | .7z+1.9+.1z=5.5-.42 | | 7x-65=43-2x | | -4(6x)= | | 5x+3(6x+15)=160 | | .0825t^2-.0924t+1.784=0 | | -12x=144 | | 1.2x+1.1=7.7-x | | 48=8 | | 18(x-1)+x=12-11x | | 3.75+7=8.1b-19.4 | | 3x+5-4x=7 | | (T-4)(t+1)=0 | | -17+3x=5x+7 | | 12w+w=5-2w | | 18+2y=4y-8 | | -2x-70=29+9x | | 3(a+7)=-6 | | 7x+5x-80=136 |

Equations solver categories